2011
DOI: 10.1016/j.chembiol.2011.04.011
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Kinase Profiling Reveals Functionally Relevant Properties of Native Kinases

Abstract: Summary Protein kinases are intensely studied mediators of cellular signaling, yet important questions remain regarding their regulation and in vivo properties. Here we use a probe-based chemoprotemics platform to profile several well studied kinase inhibitors against more than 200 kinases in native cell proteomes and reveal new biological targets for some of these inhibitors. Several striking differences were identified between native and recombinant kinase inhibitory profiles, in particular, for the Raf kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
390
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 306 publications
(401 citation statements)
references
References 42 publications
(58 reference statements)
8
390
1
2
Order By: Relevance
“…With the exception of a recent study that reported the discovery of over 800 ATP-interacting proteins in several different breast cancer cell lines using a specially designed ATP probe in combination with a targeted mass spectrometrybased approach (35), the number of protein hits identified in the current study is comparable to the 100 -200 ATP interacting proteins identified in several recent chemical proteomics studies, which also relied on specially designed ATP probes to characterize ATP-interacting proteins (30,31,36,37). The current study is the largest proteome-wide profile of an ATP-interactome using an energetics-based method, to date.…”
Section: Discussionsupporting
confidence: 51%
“…With the exception of a recent study that reported the discovery of over 800 ATP-interacting proteins in several different breast cancer cell lines using a specially designed ATP probe in combination with a targeted mass spectrometrybased approach (35), the number of protein hits identified in the current study is comparable to the 100 -200 ATP interacting proteins identified in several recent chemical proteomics studies, which also relied on specially designed ATP probes to characterize ATP-interacting proteins (30,31,36,37). The current study is the largest proteome-wide profile of an ATP-interactome using an energetics-based method, to date.…”
Section: Discussionsupporting
confidence: 51%
“…Upon follow-up IC 50 value determination, only two were inhibited by CC-223 with IC 50 values below 1 mmol/L; FLT4 (0.651 mmol/L) and cFMS (0.028 mmol/L). The exquisite kinase selectivity of CC-223 was confirmed upon evaluation in cellular systems using ActivX KiNavtiv profiling (17,18). Other than mTOR kinase, no kinase target was identified when HCT 116 or A549 cells were treated for 1 hour with 1 mmol/L CC-223 and assayed for kinase activity.…”
Section: Resultsmentioning
confidence: 99%
“…tated use of micromolar concentrations for our studies. To test target occupancy in the context of the cell, we subjected cells treated with 10 M compound 1 to analysis by ActivX technology in the KiNativ panel (23). We observed that the compound has excellent selectivity against 170 kinases in the panel with 90% occupancy against IRAK4 and only 55% occupancy against IRAK1.…”
Section: Pharmacological Inhibition Of Irak4 Kinase Blocks Irak4 Phosmentioning
confidence: 99%